Release management system an eclipse plug-in - Teo, Jasmine Wei Lin. (2009)
In this project, a release management plug-in to Eclipse is designed and developed. The plug-in, Cclipse is deployed in Eclipse and it will provide a bridge linking Bugzilla and Concurrent Version System (CVS). This will eliminate the need for release managers to manually trace the relationship between the bugs and the CVS files for a particular release. Cclipse allows release manager to visualize the bugs and its associated CVS files, manage their releases and its outstanding bugs with their corresponding files in CVS. Cclipse makes use of the components available in CVS and Bugclipse plug-ins to encourage the reuse of available libraries. These libraries are reliable as they have been extensively tested, and hence they are used in creating this plug-in. The design methodology used are explained using Unified Modeling Language (UML) diagrams and supported with software engineering concepts. A clean and concise user interface was also created to highlight the releases and their corresponding bugs to the release manager. With Cclipse, the release manager will be able to create, edit, manage his software releases and generate reports all under a single Eclipse Integrated Development Environment (IDE). He will also be able to view the releases belonging to a particular bug ID at the Bugzilla webpage. Although the fundamental requirements are met, additional features could be added to enhance Cclipse. Some recommendations include search engine support and a change of persistence storage.